VOLATILE SUBSTANCES AND ELEMENTAL COMPOSITION OF FRUITS OF SOPHORA JAPONICA L. FLORA OF UZBEKISTAN - Abdullabekova, V.N.; Abdullabekova, N.A. (The journal of contemporary issues in business and government, 2021)
The article presents the results of identification of volatile substances, as well as macro and microelement composition of fruits "Sophorajaponica L.", cultivated in Tashkent using the method of chromatomass spectroscopy on an Agilent 7890 AGS gas chromatograph, as well as mass spectral analysis using a mass spectrometer inductively coupled plasma ICP MS (inductivelycoupledplasmamass-spectrometerAgilentTechnology 7500). As a result of the studies carried out in the fruits of Sophorajaponica L., the content of α-pinene (in hexane - 26.67%, in benzene - 12.93%), eucalyptol (in hexane - 17.23%, in benzene - 9.45%) and camphor (in hexane - 4.5%, in benzene - 2.49%), and the most significant macro- and microelements were found, among which potassium, sodium, magnesium, calcium, phosphorus, manganese, iron predominate in quantitative terms, chrome, copper and zinc.